2022
DOI: 10.1186/s12931-022-02063-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between oxygen saturation level during bronchoscopy and post-bronchoscopy adverse events: a retrospective cohort study

Abstract: Background Flexible bronchoscopy is widely used to diagnose and treat various respiratory diseases. However, caution is warranted for post-bronchoscopy adverse events. Although desaturation frequently occurs during bronchoscopy, its clinical impact and the optimal oxygen saturation level during the procedure remain unclear. This study aimed to investigate whether the percutaneous oxygen saturation (SpO2) level during bronchoscopy is associated with the development of post-bronchoscopy respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“… 34 In this study, the overall incidence of LOS was 26.0% (121/465), which was consistent with that of previous published reports. 15 18 Previous studies have identified LOS as an independent risk factor for post-bronchoscopy respiratory adverse events that may worsen clinical outcomes or lead to fatal events. 18 , 35 Additionally, given the considerable restenosis rates even after bronchoscopy, PTTS patients tend to undergo bronchoscopic procedures as many times as needed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 34 In this study, the overall incidence of LOS was 26.0% (121/465), which was consistent with that of previous published reports. 15 18 Previous studies have identified LOS as an independent risk factor for post-bronchoscopy respiratory adverse events that may worsen clinical outcomes or lead to fatal events. 18 , 35 Additionally, given the considerable restenosis rates even after bronchoscopy, PTTS patients tend to undergo bronchoscopic procedures as many times as needed.…”
Section: Discussionmentioning
confidence: 99%
“…15 18 Previous studies have identified LOS as an independent risk factor for post-bronchoscopy respiratory adverse events that may worsen clinical outcomes or lead to fatal events. 18 , 35 Additionally, given the considerable restenosis rates even after bronchoscopy, PTTS patients tend to undergo bronchoscopic procedures as many times as needed. Research is, therefore, necessary for preoperatively predicting LOS risk in PTTS patients during bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations